THE IMPACT OF USING E-COLLABORATION TOOLS ON COMPANY PERFORMANCE - Rifat O. Shannak (European Scientific Journal, ESJ, 2013)
Recent advances in inter-organizational software and communication technologies, along with the trends towards globalization, networking, mass customization, and digitization in the context of the supply chain, have led to the development of ‘e-collaboration’ concept. The central premise of this research is that e-collaboration plays a major role in achieving a sustainable performance. In particular, this paper proposes to examine the relative efficiency of electronic collaboration tools and assess their impacts on the performance of an individual organization positioned along its supply chain. Empirical data from both the company and its customers have been collected for the purpose of hypothesis testing.